AB0610 SEASONAL VARIATION IN IDIOPATHIC INFLAMMATORY MYOPATHIES INCIDENCE AND PRESENTATION: A RETROSPECTIVE STUDY IN BEIJING AND HONG KONG. (2nd June 2020) - So, H.; Shen, Y.; Wong, T. L. V.; Ho, R.; Li, T.; Lu, X.
Abstract : Background: Seasonal patterns of disease onset and severity in idiopathic inflammatory myopathies (IIMs) as a whole are conflicting [1-3]. In recent years, over 10 myositis-specific antibodies (MSAs) have been identified. They are able to divide patients into homogenous subgroups and inform on prognosis [4]. Objectives: The objective of the study was to investigate the seasonal variation of onset of IIMs characterised serologically. Methods: This was a multi-centred retrospective observational study. Consecutive Chinese patients with IIMs admitted to the rheumatology wards of the participating major regional hospitals in Beijing and Hong Kong from July 2013 to June 2018 were recruited. The diagnosis of IIMs was based on the Bohan and Peter's criteria with definite or probable cases being included [5]. Patients with clinically amyopathic disease must have the typical Gottron's papules or heliotrope rash as determined by rheumatologists or dermatologists, and with no symptoms or signs of muscle involvement according to Sontheimer [6]. Patients with juvenile myositis, inclusion body myositis, cancer-associated myositis and myositis associated with other connective tissue disease were excluded. A commercial line blot immunoassay kit (EUROLINE) was used to detect the MSAs. Results: All together 495 patients were studied. The mean age of the patients at disease onset was 48.1 years (S.D. 13.3). There was a female predominance (68.3%). The subgroups of IIMs were: dermatomyositis (61.0%), polymyositis (21.8%), clinically amyopathic dermatomyositis (12.9%), immune mediated necrotising myopathy (3.8%) and nonspecific myositis (0.4%). No particular seasonal pattern in disease onset was observed in IIM patients as a whole (Figure 1 ) or in any classical subgroups. However, significantly more patients with any one MSA had their disease started in the first half of the year (p=0.007) as shown in Figure 2 . Patients with either anti-synthetase or anti-MDA5 antibodies, which are associated with interstitial lung disease, had more frequent disease onset from November to February, which might coincide with the local flu season. It was also found that MSA positivity was associated with infection of the patient (p=0.005). Further analyses showed that patients with MSAs which are typically associated with severe skin disease (MDA5, TIF1g, NXP2, SAE) had more hospitalisation from April to September where excessive sun exposure is expected. There were no major differences between the Beijing and Hong Kong subgroups. Conclusion: Apparent seasonal patterns were noticed in our ethno-serologically defined IIM patients. Certain environmental factors, particularly infection or UV exposure, could be potential triggers. Our findings could shed light on the identification of etiologic factors and enhance our understanding of disease pathogenesis. References: [1]Manta P, Kalfakis N, Vassilopoulos D. Evidence for Seasonal Variation in Polymyositis. Neuroepidemiology 1989;8:262–265. [2]Phillips BA, Zilko PJ, Garlepp MJ, et al. Seasonal occurrence of relapses in inflammatory myopathies: a preliminary study. J Neurol 2002;249:441–4. [3]Lefe R, Burgess S, Miller F, et al. Distinct Seasonal Pattern in The Onset of Adult Idiopathic Inflammatory Myopathy in Patients with Auto Antibodies Anti-Jo-1 and Anti-Signal Recognition particle. Arthritis and Rheumatism 1991;34(11):1391-1396. [4]Tansley SL, Betterridge ZE, McHugh NJ. The diagnostic utility of autoantibodies in adult and juvenile myostis. Curt Opin Rheumatol 2013;25(6):772-777. [5]Bohan A, Peter JB. Polymyositis and dermatomyositis. N Engl J Med 1975;292:344-347. [6]Sontheimer RD. Clinically myopathic dermatomyositis: what can we now tell our patients? Arch Dermatol 2010;146(1):76-80. Disclosure of Interests: None declared